Refining the environmental and climatic background of the Middle Pleistocene human cranium from Gruta da Aroeira (Torres Novas, Portugal) - López-García, Juan Manuel (2019)
The recent publication of a human cranium, dating to ca. 436e390 ka, from Gruta da Aroeira provides an important input to the debate about human evolution during the Middle Pleistocene in Europe and the origin of the Neanderthals. This cranium, chronologically located to Marine Isotope Stage 11c (MIS 11c), appears in association with Acheulean lithic tools and several faunal remains, among which cervids and equids are predominant. The small vertebrate assemblage associated with the Aroeira-3 cranium suggests an environment and a climate related to an open-woodland landscape and relatively mild and humid conditions, probably in connection with the end of MIS 11c. Moreover, comparison with other Middle Pleistocene Iberian sites with human remains suggests that these hominins lived in open forest areas during mild climatic substages.